Analysis of Natural Resource Impacts Post-Operation of PT X in Gorontalo Village: Analisis Dampak Sumber Daya Alam Pasca Operasional PT X di Desa Gorontalo - Aditya Reyhan Prasetyo; Restu Hikmah Ayu Murti (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Hotel operational activities have a significant impact on the surrounding environment, both positively and negatively. The main focus of this study is to identify changes in environmental quality and natural resources that occur after the hotel operates, and to assess the potential for environmental sustainability to be maintained. Descriptive analysis methods were used to collect data through observation, interviews, and documentation studies. The data obtained were then analyzed to describe the condition of natural resources after the hotel operates. The results of the study indicate that there are significant changes in the quality of clean water, wastewater, and seawater, as well as an increase in noise and generator emissions. However, the presence of the hotel also has a positive impact in the form of increasing the local community's economy through employment opportunities and the tourism sector. The results of the study provide recommendations on the need for planned mitigation efforts through better waste management, improved environmental quality monitoring systems, and collaboration between the hotel and the community in maintaining the sustainability of natural resources. With the right approach, negative impacts can be minimized and environmental sustainability can be maintained in the long term.